The directional and non‐directional associations of periodontitis with chronic kidney disease: A systematic review and meta‐analysis of observational studies. (18th May 2018) - Zhao, D.; Khawaja, A. T.; Jin, L.; Li, K.‐Y.; Tonetti, M.; Pelekos, G.
Abstract : This systematic review aimed to assess the current evidence on the directional and non‐directional associations of periodontitis with chronic kidney disease (CKD). Electronic search for observational studies on the association of periodontitis with CKD was performed in MEDLINE, EMBASE, PubMed, Open GREY and Cochrane library up to June 5, 2017. Two reviewers conducted study selection, data collection and assessment of methodological quality using the original and modified Newcastle‐Ottawa Scale. Cohort, case‐control and cross‐sectional studies were included, which clearly defined periodontitis and CKD or reported acceptable clinical parameters of these 2 diseases in adults. Meta‐analysis was employed to estimate the pooled odds ratio on the non‐directional association and the incidence rate ratio (IRR) for the directional association. Among 2530 potential eligible articles, 47 were finally included. Most of them investigated a non‐directional association of periodontitis with CKD, including 7 case‐control studies and 38 cross‐sectional studies; 24 studies had statistical analysis on the non‐directional association and 75% of them reported significant results, which were supported further by the meta‐analysis (random: odds ratio = 2.12, P  < .001; χ 2  = 25.74, I 2  = 88.3%). None of the studies focused on the directional association of CKD (as the exposure) with periodontitis (as the outcome), whereas 2 retrospective cohort studies explored a directional association of periodontitis (as the exposure) with CKD (as the outcome) (random: IRR=2.10, P  > .05; fixed: IRR=1.76, P  < .05; χ 2  = 4.65, I 2  = 78.3%). Overall, the high heterogeneity of studies limits the significance of these results. There is substantial evidence on the non‐directional association of periodontitis with CKD, while there are limited studies on the directional association. Well‐designed prospective studies with longer follow‐ups in representative communities are needed to clarify the directional association and enhance the quality of the evidence on this topic.